Current Pharmacological Treatment of Pulmonary Aspergillosis. Issue 5 (September 2015) - Bassetti, Matteo; Carnelutti, Alessia; Righi, Elda; Corcione, Silvia; De Rosa, Francesco G.
<x xml:space="preserve">Abstract</x> Invasive aspergillosis (IA) is a severe condition with high mortality rates that typically occurs among immunocompromised patients, mostly those affected by hematological malignancies. In the past few years, an increasing number of cases have been reported among patients without classic risk factors. Although the current guidelines report voriconazole as the first-line therapy for IA, the increase in the rates of Aspergillus fumigatus resistant to azoles represents an emerging problem and requires the introduction of new therapeutic options. For these reasons, alternative antifungal therapies may be used in selected scenarios. The 2014 European Society of Clinical Microbiology and Infectious Disease guidelines recommend the use of isavuconazole, a new azole, as one of the first-line treatments for IA, and liposomal amphotericin B with a lower strength of recommendation; other lipid formulations of amphotericin B, posaconazole, and caspofungin can be used as second-line or salvage therapy. More studies are awaited to investigate the benefits of antifungal combination therapies in IA.